Efficiency in Violence: Analyzing Israel's War Crimes in Gaza through the Economic Analysis of Law Approach - Andranurviza, Rachmayani; Dita, Rohmadtika; Tifani, Nyala Candrika; Hakiki, Muhammad Ikhwan (Social and Economic Bulletin, 2025)
This paper examines the war crimes committed by Israel in Gaza following the events of October 7, 2023, using the Economic Analysis of Law (EAL) approach through the lens of international relations. The EAL approach is used to show how that the country blatantly disregards the set legal provisions and continues to violate human rights. The qualitative method and normative-empirical analysis help to understand the rationality behind Israel’s actions based on cost-benefit calculations within EAL theory. The study’s findings indicate that Israel’s actions are rational due to the economic benefits gained—military dominance, domestic political support, and strategic advantages—which are made possible by weak enforcement of international law. The paralysis of organizations such as the UN and ICC in enforcing laws and imposing sanctions further reinforces this dynamic. As a result, the study highlights the need for legal reform and enforcement within global governance to prevent similar violations by powerful nations in the future. It also contributes to discussions on legal accountability in international conflicts and underscores the importance of restructuring incentives within the international legal system to uphold justice and protect human rights on a global level.